GEREJA UNIVERSAL DALAM ALKITAB: Universal Church in The Bible - Kasakeyan, Raimond Heintje (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Understanding the concept of the church is essential in the history of Christianity. There are too many confusing teachings, thus clouding the view of Christians. The best approach to "church" theology is to look at the use of New Testament terms to mean "church." This paper is a literature study that aims to present information and arguments regarding the Biblical Universal Church as a concept that should be clearly understood by every Christian. This understanding should have an effect in reducing and even reducing conflicts related to disputes and divisions that generally exist in any church, and is also one of the most important factors in the growth of the local church according to Bible teachings. The Bible presents several images, namely: the Flock of God's Lamb, the Vine, the Building of God, the Body of Christ, the Bride of Christ, God's People and God's Family. These images are used to explain Christ's relationship with His church by emphasizing the unity that is at the core of how God wants us to experience life together in His church. Every born-again believer is in that unity as one universal church, even if he comes from a different church denomination, united in one faith, one hope, and one love. getting closer to each other